Comparing Hip Dysplasia in Dogs and Humans: A Review - Willemsen, Koen; Möring, Michelle M.; Harlianto, Netanja I.; Tryfonidou, Marianna A.; van der Wal, Bart C. H.; Weinans, Harrie; Meij, Björn P.; Sakkers, Ralph J. B. (Frontiers in Veterinary Science, 2021)
Hip dysplasia (HD) is common in both humans and dogs. This interconnection is because humans and dogs descended from a common ancestor and therefore have a similar anatomy at micro- and macroscopic levels. Furthermore, dogs are the animals of choice for testing new treatments for human hip dysplasia and orthopedic surgery in general. However, little literature exists comparing HD between the two species. Therefore, the aim of this review is to describe the anatomy, etiology, pathogenesis, diagnostics, and treatment of HD in humans and dogs. HD as an orthopedic condition has many common characteristics in terms of etiology and pathogenesis and most of the differences can be explained by the evolutionary differences between dogs and humans. Likewise, the treatment of HD shows many commonalities between humans and dogs. Conservative treatment and surgical interventions such as femoral osteotomy, pelvic osteotomy and total hip arthroplasty are very similar between humans and dogs. Therefore, future integration of knowledge and experiences for HD between dogs and humans could be beneficial for both species.